Sustainable governance indicators 2018 Turkey report - GENÇKAYA, ÖMER FARUK (Bertelsmann Stiftung, 2018)
The period under review was marked by deep political and social divisions in Turkey. The failed coup attempt of 15 July 2016, and the subsequent state of emergency has changed the course of Turkish politics and increased uncertainty. The government’s politically charged allegations, judicial investigations and dismissal of thousands of civil servants, and the immense organizational capacity of the Gülenist movement in the public and private sector brought public trust to rock-bottom levels. Rising popular authoritarianism has undermined the rule of law, legal certainty and judicial independence, exacerbated widespread social discrimination, and reinforced the presidential model and exclusion of the legislature from governmental processes. The chair of TÜSİAD, Turkey’s leading business association, stated “Judicial independence and impartiality, freedom of thought and expression, a free and scientific academic environment, free media and internet, welldefined authorities and responsibilities, and a meritocratic public administration are important parameters of a country’s competitive political system, which Turkey currently lacks. Domestic and international challenges require a new economic, political and social grand strategy for Turkey in order to raise the level of sustainable governance.” The war in Syria has had a profound impact on Turkish politics and society. The terrorist attacks in Suruc, Ankara and Istanbul, the massive inflow of Syrian refugees, and the emergence of the Islamic State group have fueled tensions across the country and presented the government with major political challenges. The government’s extensive military counterinsurgency in predominantly Kurdish provinces in the southeast of Turkey and attacks by terrorist-designated groups – such as the Kurdistan Workers’ Party (PKK) and the Kurdistan Freedom Hawks – signified an end to the peace process between the Turkish state and PKK, which had shown significant promise in recent years. The government appears to lack a clear strategy for ending the conflict in Turkey’s southeast region. This not only hampers economic opportunities in the southeast, but will also undermine democratic governance in the years ahead. Indeed, throughout the review period, the government continued to respond to dissent with repressive tactics, including openly threatening perceived opponents (e.g., activists, academics or journalists). Many journalists critical of the government now operate under financial threats, selfcensorship and increased job insecurity. Although the number of civil society organizations increased during the review period, their influence in decision-making processes remains limited. The massive polarization between pro- and anti-government camps is present across all spheres of political, economic and social life. The negative effects of this divide were evident in the aftermath of the parliamentary elections on 7 June 2015, which failed to deliver a coalition government in line with the constitution. This inability and/or unwillingness to engage in a power-sharing agreement demonstrates a serious crisis of democracy in Turkey. The election marked the first time in modern Turkish history that civilian politicians refused to accept a parliamentary election result and reach a cross-party compromise. The Justice and Development Party (AKP) secured an absolute parliamentary majority during the November 2015 parliamentary election, allowing the AKP to rule alone for the fourth time since 2002. Electoral fairness, the AKP’s use of state resources and the lack of campaign finance transparency were major issues in both the June and November 2015 parliamentary elections. Throughout both elections, the AKP failed to fully implement the recommendations of the Group of States against Corruption (GRECO) on campaign and party funding. The use of languages other than Turkish was permitted in both elections. Despite strengthening antidiscrimination efforts, Alevis and Roma people still lack access to basic public services. Moreover, anti-Semitism in Turkish politics and society remains widespread. Authorities have begun to address gender discrimination, but violence against women persists, and there has been no improvement in the educational attainment and economic participation gender gaps. The inflow of Syrian refugees is likely to have serious social, economic and political implications for Turks and Syrians living in Turkey. At the time of writing, there are more than three million Syrian refugees in Turkey. Over the last decade, Turkey has experienced important gains in income and living standards. Though economic competitiveness has decreased, recently. While economic growth has returned after the 2016 economic slowdown, such positive signs are based on the availability of cheap and abundant money, which increases demand (higher consumption and public expenditure) rather than efficiency. Environmental sustainability, energy security, sustainable urban development and progress toward a high-tech, science-based society are not assured. However, increased government spending (e.g., on research and development, education and vocational training, social policy and health care) during the review period marked a step forward, but so far fails to show sustainable results.